(untitled) (Research, Society and Development, 2022)
Objective: to report a nursing visit experience at the bedside and present a construction of a systematic guide to improve this activity and facilitate the passage of the plant. Methodology: an experience report that emerges from the academic experiences of the undergraduate nursing course during the practices of the Supervised Hospital Internship. Results: a nursing visit at the bedside provides a broad view on the clinical conditions of patients and, the development of nursing diagnoses and exams most used with basic human needs and the availability of an instrument as a script, provides opportunities a coherent and aligned practice among nurses. Final considerations: the experience lived and here Register about making visits to the bedside with the help of a contribution script with academics in the field of practice, as well as with assisting nurses. The construction of this instrument, of the systematic guide type, provides a reflection on the perspective of an instrument that can facilitate and add the quality of the nurse’s work process in hospital areas.